Management of Educational Facilities and Infrastructure in Islamic Junior High School - Rizky, Diannisa; Karnati, Neti; Supadi, Supadi (LPPM Undiksha, 2022)
One of the efforts to improve the quality of Indonesia's young generation is through the learning process in schools, and successful learning is supported by the effective and efficient utilization of all educational facilities and infrastructure in schools. This study aims to analyze the planning, procurement, inventory, maintenance, and removal of educational facilities and infrastructure at one of Islamic Junior High School. A qualitative research data collection technique is used through observation, interviews, documentation, and triangulation. Data analysis techniques procedure including: data collection, data reduction, data presentation, and concluding. The subjects in this study were students and teachers. Based on the results of the study it can be seen: first, planning activities for facilities and infrastructure are always carried out starting from analysis, determining funds, and selecting needed goods, second procurement activities are carried out by buying and determining funds as needed, the third inventories are always carried out as evidence of the procurement of goods, and coding is carried out when the goods come to school, the fourth maintenance of facilities and infrastructure is carried out regularly by involving school residents and discussed through periodic meetings, fifth Deletion activities are carried out if there are inappropriate goods, damaged goods, and goods that are no longer used.